The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.5006/0749
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Resistance Spot Welding and Post-Welding Sensitization on the Pitting Corrosion Behavior of AISI 304 Stainless Steel

Abstract: This work studies the combined effect of resistance spot welding and post-welding sensitization on the pitting corrosion behavior of AISI 304 (UNS S30400) by using cyclic potentiodynamic polarization tests. The combined effect of welding and post-welding sensitization give rise to worse pit nucleation resistances and better repassivation capacities than those of the state without prior welding. This behavior is caused by the weld metal zone, a cast dendritic microstructure with δ-ferrite in interdendritic regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…As it can be observed in Figures 13 and 14, the variation rate of the DOS with post-welding sensitisation time is higher in the FZ than in HAZ and BM. This phenomenon is caused by the fact that the kinetics of microstructural regeneration is faster in FZ than in HAZ and BM [24,65], which may be due to two causes. First, the chemical segregation associated with the solidification processes [66,67], where the last fraction of liquid that solidifies enriches in ferrite-stabilising elements such as chromium, and thus, the interdendritic regions can be expected to be zones for preferential delta-ferrite formation [68,69] (this chemical segregation makes the rate of diffusion higher since concentration gradient is, according to Fick's law, the driving force of diffusion [70]).…”
Section: Resultsmentioning
confidence: 99%
“…As it can be observed in Figures 13 and 14, the variation rate of the DOS with post-welding sensitisation time is higher in the FZ than in HAZ and BM. This phenomenon is caused by the fact that the kinetics of microstructural regeneration is faster in FZ than in HAZ and BM [24,65], which may be due to two causes. First, the chemical segregation associated with the solidification processes [66,67], where the last fraction of liquid that solidifies enriches in ferrite-stabilising elements such as chromium, and thus, the interdendritic regions can be expected to be zones for preferential delta-ferrite formation [68,69] (this chemical segregation makes the rate of diffusion higher since concentration gradient is, according to Fick's law, the driving force of diffusion [70]).…”
Section: Resultsmentioning
confidence: 99%
“…The literature review reveals that a lot of work has been reported on sensitization phenomenon while RSW of SS [5][6][7][8][9] . Some studies have focused on the combined effect of resistance spot welding and post-welding sensitization on the pitting corrosion behavior of AISI 304 SS 10 . But hitherto no work has been reported as comparative study on the performance of cryogenically treated and non-cryogenically treated welding electrodes for reducing sensitization related problems in RSW of 304SS.…”
Section: Introductionmentioning
confidence: 99%